Evaluasi Kualitas Hidup Pasien Kanker Serviks yang Mendapat Regimen Kemoterapi Cisplatin-Vinkristin-Bleomisin dan Carboplatin-Paklitaksel - Suwendar Suwendar; Achmad Fudholi; Tri Murti Andayani; Herri S. Sastramihardja (Faculty of Pharmacy, Universitas Gadjah Mada)
Cervical cancer is one type of cancer with a high prevalence in women. Quality of life of someone with cervical cancer will decrease. Quality of life can also decrease because of chemotherapy regimens. The purpose of this study was to evaluate the impact of cisplatin-vincristine-bleomycin and carboplatin-paclitaxel regimens on the quality of life of patients. Through this research how the difference in quality of life of patients with cervical cancer before and after chemotherapy could be known. Additionally, the differences impact on the quality of life of the two regimens also were observed. The study was conducted by using cross sectional design in hospitalization patients. Data were taken prospectively by conducting field observations. Measuring the quality of life was done using the EORTC QLQ-C30 questionnaire. Differences of domain values before and after chemotherapy in each regimen were analyzed by paired t-test (p <0.05). Quality of life difference between two regimens were analyzed by unpaired t test (p<0.05). The results showed that there was an increasing trend of the value of the functional domain, impairment of symptoms domain and an increase in the value of global health status domain after three cycles of chemotherapy of two regimens, except the symptoms of nausea and vomiting and loss of appetite that showed an increasing trend. Patients who received cisplatin-vincristine-bleomycin regimen showed a significant increasing (p = 0.009) in decreased of appetite symptom’s scores. No significant differences in the quality of life of patients who delivered chemotherapy regimen of cisplatin-vincristine-bleomycin compared to carboplatin-paclitaxel regimen.